Effectiveness and Safety of Additive Therapy and Monotherapy of Glaucoma with Prostamides - I. R. Gazizova; S. R. Zainullina; E. B. Martynova (Oftalʹmologiâ)
Increased intraocular pressure (IOP) is the main risk factor for the development of primary open-angle glaucoma (POAG). Nowadays medicine that reduce IOP remain the main method of treating for POAG. The first-line drugs for POAG are prostaglandin analogues. In Russia, for the first time, it appeared not in the form of a fixed combination (Bimoptic). In this regard it is very important to evaluate the clinical efficacy and safety of Bimoptic as a monotherapy and additive component in the treatment of patients with POAG. Patients and methods. Patients were divided into 3 groups depending on the treatment. Group I comprised of 34 patients with newly diagnosed glaucoma on monotherapy with bimatoprost 0.03 %. Group II consisted of 30 patients who started taking bimatoprost 0.03 % as a replacement for latanoprost 0.005 % or travoprost 0.004 %. There were 32 patients in group III, who were prescribed bimatoprost 0.03 % as an adjuvant therapy for B-blockers (BB) 0.5 % or carbonic anhydrase inhibitors (ICA) 2 %. Results. According to the results of the clinical study, it was found that instillation of Bimoptik as a monotherapy for newly diagnosed POAG leads to a decrease in IOP level by an average of 32.1 % of the initial level. With the additive tactics of assigning Bimoptik to the BB and / or IKA, the level of IOP goes down by 10.6 % more. If prostaglandin is changed to Bimoptik, the level of IOP decreases by 12.6 % of the prostaglandin-associated values. Also according to acquired data, Bimoptik has a low percentage of adverse reactions, slight hyperemia and discomfort were observed in 5.2 % of cases in all groups. Conclution. Bimoptik effectively reduces the level of IOP in both monotherapy and additive tactics with the least adverse reactions.